2018
DOI: 10.1002/wcs.1466
|View full text |Cite
|
Sign up to set email alerts
|

Phonological regularity, perceptual biases, and the role of phonotactics in speech error analysis

Abstract: Speech errors involving manipulations of sounds tend to be phonologically regular in the sense that they obey the phonotactic rules of well-formed words. We review the empirical evidence for phonological regularity in prior research, including both categorical assessments of words and regularity at the granular level involving specific segments and contexts. Since the reporting of regularity is affected by human perceptual biases, we also document this regularity in a new data set of 2,228 sublexical errors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 92 publications
1
11
1
Order By: Relevance
“…Likewise, the deletion of syllable final [p] in sa [p] → sa results in the short vowel [a] in an open syllable, which is again outlawed by Cantonese phonotactics. The frequency of errors with phonotactic violations is 10.8%, which is a bit higher than what has been reported for English (Alderete & Tupper, 2018). This may be due to the relatively high number of non-native sounds in the Cantonese corpus, which accounts for roughly half of these cases.…”
Section: 4contrasting
confidence: 56%
See 2 more Smart Citations
“…Likewise, the deletion of syllable final [p] in sa [p] → sa results in the short vowel [a] in an open syllable, which is again outlawed by Cantonese phonotactics. The frequency of errors with phonotactic violations is 10.8%, which is a bit higher than what has been reported for English (Alderete & Tupper, 2018). This may be due to the relatively high number of non-native sounds in the Cantonese corpus, which accounts for roughly half of these cases.…”
Section: 4contrasting
confidence: 56%
“…There are, nevertheless, certain kinds of errors that are unambiguously segmental for the simple fact that they are impossible syllables. While sound errors tend to obey phonotactic rules (Boomer & Laver, 1968;Wells, 1951), meaning that sounds generally slip into well-formed syllables, recent evidence has shown that this constraint is far weaker than previously assumed (Alderete & Tupper, 2018).…”
Section: 4mentioning
confidence: 93%
See 1 more Smart Citation
“…Human subjects are able to evaluate and produce nonce-words even if a string of phonemes violates language-specific phonotactics, as long as the basic universal phonotactic requirements that treat phones as atomic units are satisfied (for an overview of phonotactic judgments, see Ernestus, 2011 and literature therein). Deleting or inserting segments are also common patterns in both L1 acquisition (Macken and Ferguson, 1981), loanword phonology (Yildiz, 2005), in children with speech disorders (Catts and Kamhi, 1984;Barlow, 2001), as well as in speech errors (Alderete and Tupper, 2018b). For example, #sT clusters are often simplified in L1 acquisition (Gerlach, 2010).…”
Section: Parallels In Human Behaviormentioning
confidence: 99%
“…For example, Stemberger (1983) reported that only 1% of the phonological errors in his English slip corpus overtly violated English phonotactics. This 1% rate of violations is likely an underestimate, though, because of perceptual biases that can occur during error collection (Alderete & Davies, 2019; Alderete & Tupper, 2018).…”
mentioning
confidence: 99%